A phenomenological exploration of coping responses associated with choking in sport - Denise Hill (Qualitative Research in Sport, Exercise and Health, 2015)
The likelihood of choking in sport is moderated by the athlete’s choice of coping strategy. Yet a lack of consensus exists with regards to which strategies encourage or prevent the choke. Accordingly, the aim of this study was to explore, through qualitative methods, the coping responses perceived to be associated with choking episodes. Semi-structured interviews were completed with six elite golfers who had experienced both choking and clutch performances under pressure. It was revealed that avoidance coping strategies (e.g. rushing and denial) were considered to precede and/or accompany their choking episodes, whilst approach coping strategies (e.g. pre- and post-shot routines, cognitive restructuring and simulated practice) were associated with their clutch performances. Such findings are discussed within the context of the extant choking literature, and used to inform recommendations for practitioners working with choking-susceptible performers.